Application of Buchanan methodology for the construction of an expert system with bayesian networks to support the diagnosis of tetralogy of Fallot in Perú - Delgado Montenegro, Linda (2016)
This research addresses the problem related to congenital heart disease. Prompt medical diagnosis in the case of disease risk, such as congenital heart disease, becomes a key for appropriate treatment, in this context the lack of infrastructure and trained personnel becomes a latent problem that can have consequences fatal. Buchanan methodology was used because after the evaluation found that the project needs and the benefits of its implementation was adapted. The development project is justified because it provides a logical systematization of knowledge in the area of heart disease that will serve as support for the completion of due diagnostic tool,benefiting greatly to health services in the pediatric area at national.